Pharmaceutical prices under regulation: Tiered co-payments and reference pricing in Germany - Annika Herr; Moritz Suppliet (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
Many countries with national health care providers and health insurances regulate the market for pharmaceuticals to steer drug demand and to control expenses. For example, they introduce reference pricing or tiered co-payments to enhance drug substitution and competition. Since 2006, Germany follows an innovative approach by differentiating drug co-payments by the drug's price relative to its reference price. In this two-tier system, prescription drugs are completely exempted from co-payments if their prices undercut a certain price level relative to the reference price. We identify the effect of the policy on the prices of all affected prescription drugs and differentiate the analysis by firm types (innovative, generic, branded generic or importing firms). To identify a causal effect, we use a differences-in-differences approach and additionally exploit the fact that the exemption policy had been introduced successively in the different clusters. We use quarterly data from 2007 to 2010 and find empirical evidence for differentiated price setting strategies by firm types, ranging from price decreases of -13.1% (branded generics firms) to increases of +2.0% (innovators) following the introduction of potential reductions in co-payments. We refer to the latter result as the co-payment exemption paradox. Our competition proxy (no. of firms) suggests a significant but small negative correlation with prices.
Keywords: D22; D40; I18; I11; L11; 330; pharmaceuticals; prices; co-payments; reference pricing; regulation; firm behavior